Optimization of friction stir welding process parameters using multi-criteria decision making approach - Ay, Mustafa; Sarsilmaz, Furkan (Walter de Gruyter Gmbh, 2023)
In this study, two different aluminum alloy (AA1030/AA7075) pairs were joined using friction stir welding (FSW) method. Tool rotation speed, welding speed, and stirrer geometry were chosen as variable welding parameters. The welded joint zones were evaluated for both microstructural and mechanical properties such as ultimate tensile strength (UTS) and nugget hardness (H). Optimum welding parameters were determined using multi-criteria decision making techniques such as rank preference technique by similarity to ideal solution (TOPSIS) and gray relational analysis (GRA). At the same time, the performances of the TOPSIS and GRA methods were compared.
Keywords: Al alloys; FSW; multi-criteria decision making techniques; TOPSIS and GRA approach